Prophylactic and therapeutic effects of EsV3 on atherosclerotic lesions in ApoE−/− mice - Yaze Wang; Hifumi Ohishi; Rongji Wu; Hui Liu; Rong Xu (BMC Cardiovascular Disorders)
Abstract Background Atherosclerosis (AS) is a major contributor to vascular disorders and represents a significant risk to human health. Currently, first-line pharmacotherapies are associated with substantial side effects, and the development of atherosclerosis is closely linked to dietary factors. This study evaluated the effects of a dietary supplement, EsV3, on AS in apolipoprotein E (ApoE) −/− model mice. Methods The study utilized a high-fat diet-induced ApoE−/− hyperlipidemic mouse model. EsV3 was administered in prophylactic (P-EsV3) and therapeutic regimens for 16 and 12 weeks, respectively, with distinct high- and low-dose groups (0.36 and 1.8 g/kg/day). Serum lipid levels were measured and monitored for body weight and food consumption alterations in murine models. Aortic oil red O staining was conducted to assess plaque formation and calculate the plaque-to-vessel area ratio. Liver tissue changes were examined via HE staining. Moreover, serum oxidative stress markers (MDA, GSH, SOD) were measured to evaluate oxidative damage and lipid metabolism. Results Both atorvastatin and P-EsV3 treatments significantly lowered TC, TG, and LDL-C levels, with P-EsV3-H enhancing HDL-C levels (P < 0.05). Prophylactic EsV3 administration was more effective than therapeutic administration in regulating TG and LDL-C levels and had comparable effects to atorvastatin on TC and HDL-C. All treatment groups exhibited reduced body weight compared to the model group, with no significant differences in food intake. Additionally, EsV3 administration significantly reduced the aortic plaque area and liver lipid droplets compared to the model group, while mitigating oxidative stress, as evidenced by decreased MDA levels and increased SOD and GSH levels, with outcomes comparable to those observed with atorvastatin. Conclusions In ApoE−/− hyperlipidemic mice, EsV3 improved lipid profiles and reduced aortic plaque formation. EsV3's effects, attributed partly to its antioxidant properties, were comparable to atorvastatin, suggesting its potential as a preventive and therapeutic agent for hyperlipidemia and atherosclerosis.